Efficient, thermally stable poly(3-hexylthiophene)-based organic solar cells achieved by non-covalently fused-ring small molecule acceptors. Issue 2 (20th December 2021) - Han, Daehee; Han, Yunghee; Kim, Youngkwon; Lee, Jin-Woo; Jeong, Dahyun; Park, Hyeonjung; Kim, Geon-U; Kim, Felix Sunjoo; Kim, Bumjoon J.
Abstract : We develop a non-covalently fused ring acceptor, CPDT–ICMe, to achieve P3HT -based organic solar cells with high-performance (8.17%) and excellent thermal stability. Abstract : Organic solar cells (OSCs) based on poly(3-hexylthiophene) (P3HT ) have achieved a significant enhancement of the power conversion efficiency (PCE), mainly driven by the development of non-fullerene small-molecule acceptors. However, their relatively poor thermal stability, in terms of blend morphology and concomitant performance, limits their application. Herein, we develop a non-covalently fused-ring acceptor (NFRA), denoted as CPDT–ICMe to achieve high-performance and thermally stable P3HT -based OSCs. Non-covalent interactions in CPDT–ICMe impart high planarity to its molecular backbone and facilitate strong intermolecular packing. A resulting P3HT :CPDT–ICMe OSC demonstrates superior electrical properties and a high PCE of 8.17%. Importantly, the P3HT :CPDT–ICMe OSC exhibits excellent thermal stability, maintaining 98.4% of initial PCE after 100 h of thermal annealing at 120 °C. This is attributed to the high glass transition temperature ( T g ) of the amorphous fraction of CPDT–ICMe in the blend. Under thermal stress (at temperatures up to 120 °C), molecular motion and diffusion are limited, preventing severe molecular aggregations and macrophase separations. Thus, this work provides important guidelines for the design of NFRAs for highly efficient and thermally stable P3HT -based OSCs.